Environmental Terrorism and Poverty in the Niger Delta: The Mosquitoes2019; Character of the Multinational Corporations (Global Journal of Human-Social Science, 2019)
There is no gainsaying that the Niger Delta is like a beautiful damsel raped severally with her supposed protector pretending to be defending her while collaborating with the rapists exposing her to more violations The advent of oil extraction in the region has only left it more despoiled than one can imagine The ungodly and poorly regulated romance of the Multinational Oil Corporations the Nigerian State and the oil-bearing producing communities can best be described as dangerous Mosquitoes perching on the very testicle of an old man and any attempt to kill it spells trouble Leaving it will equally mean exposing the man to acute malaria This paper examines the precarious situation of poverty in the Niger Delta induced by the very activities of MNOCs operating without respect to international environmental best practices Attempts at checking the situation seem to have fallen on deaf ears and in most cases military repression on the part of the government that should protect her citizens whose livelihoods have been bastardized with reckless abandon and impunity
Keywords: environmental terrorism; poverty; multinational oil corporations; niger delta